2017
DOI: 10.1007/s10618-017-0513-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual analysis of pressure in football

Abstract: Modern movement tracking technologies enable acquisition of high quality data about movements of the players and the ball in the course of a football match. However, there is a big difference between the raw data and the insights into team behaviors that analysts would like to gain. To enable such insights, it is necessary first to establish relationships between the concepts characterizing behaviors and what can be extracted from data. This task is challenging since the concepts are not strictly defined. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 69 publications
0
81
1
Order By: Relevance
“…Thus, in the ground transportation domain [12], analysis tasks may require clustering of trajectories according to their parts on highways, or during rush hours, or within congested areas. In football analysis [11], relevant parts of players' trajectories may need to be clustered taking into account ball possession, position on the pitch, and direction and speed of the movement. As the notion of relevance may change throughout the analysis process, interactive filtering tools should enable dynamic modification of the relevance masks, and the clustering needs to be done without destroying the original trajectories due to extracting only relevant parts.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in the ground transportation domain [12], analysis tasks may require clustering of trajectories according to their parts on highways, or during rush hours, or within congested areas. In football analysis [11], relevant parts of players' trajectories may need to be clustered taking into account ball possession, position on the pitch, and direction and speed of the movement. As the notion of relevance may change throughout the analysis process, interactive filtering tools should enable dynamic modification of the relevance masks, and the clustering needs to be done without destroying the original trajectories due to extracting only relevant parts.…”
Section: Resultsmentioning
confidence: 99%
“…Our survey consisted of a set of pairs of players randomly generated by a two-step procedure, defined as follows: First, we randomly selected 35% of the players in the dataset. Second, for each selected player u, we cyclically iterated over the ranges [1,10], [11,20], and [21, ∞] and selected one value, say x, for each of these ranges, and then picked the player being x positions above u and the one being x positions below u in the role-based ranking (if they exist). This generated a set P of 211 pairs involving 202 distinct players.…”
Section: Validation Of Playerankmentioning
confidence: 99%
“…We found that c maj = 68% and c una = 74%, indicating that PlayeRank has in general a good agreement with the soccer scouts, compared to the random choice (for which c maj = c una = 50%). Figure 11 offers a more detailed view on the results of the survey by specializing c maj and c una on the three ranges of ranking differences: [1,10], [11,20], [21, ∞]. The bars show a clear and strong correlation between the concordance among scouts' evaluations (per majority or unanimity) and the difference between the positions in the ranking of the checked pairs of players: When the ranking difference is ≤10 it is c maj = 59% and c una = 61%; for larger and larger ranking differences, PlayeRank achieves a much higher concordance with experts, which is up to c maj = 86% and c una = 91% when the ranking difference is ≥20.…”
Section: Validation Of Playerankmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the quality of passes by means of distance, shot strength, and pressuring of the receiving player is evaluated. A general visual analysis approach for pressure in soccer matches has been introduced by Andrienko et al [5]. Perl et al [38] propose the analysis of tactical performance, based on a combination of pattern recognition with neural networks and analysis of ball possession.…”
Section: Sports Analysismentioning
confidence: 99%